El efecto del Reintegro Tributario en el flujo de liquidez de las empresas beneficiadas del departamento de San Martin - Bardález Alvarado, Bessy (2004)
The present work gathers the worry of the managerial community, of the professional of the countable sciences, of the university students and of the resident of the department of San Martin of knowing the effects in the economic and commercial development in the companies of the department that market products that have the benefit of the refund of the general tax to the sales. To give an answer to this worry it was proposed like a study base, the influence of the tributary refund in the liquidity, handling of price and investment in the companies of the department of San Martin, being proceeded to pick up financial and administrative information through surveys, designed by the authors, with which the analysis, conclusions and recommendations were made. lt was taken as population to the quantity of companies of the department of San Martin that market benefited products and which requested the refund from de general tax to the sales in the exercise 2002 to whom all the financial and administrative information was requested. To carry out the analysis all the information was picked up, regarding the financial part, of the financial states (General Balance and State Of Lost and Earnings) being also used as analysis methods: the horizontal, vertical and of ratios analysis; applying them to the exercises 2001 (base year) and 2002 ( analysis year ) to compare the evolution from one year to another. The administrative information was requested through surveys, designed especially for the aims of the investigation, in which is required to the detail specific aspects of the administrative handling of the liquidity, handling of the prices and the investment generated by the refund from the general tax to the sales, being exposed this information through squares summarizes that were designed with the purpose of analyzing this. The most important limitation that we had for the realization of the project was an investigation design (experimental) which was proposed at the beginning and it was impossible to execute it adapting in the process a new design (descriptive) that fitted to our reality; getting in the same way the purpose of the realized investigation. When the analysis of the financial and administrative aspect was made, coincidences with the outlined hypothesis were found, arriving to worrying, conclusions in comparison to the purpose that pursues the tributary benefit of the refund from the general tax to the sales, for instance the fact of impacting in form negative in the liquidity of the companies that use the mentioned refund, for the delay in their refund, personnel 's lack for the resolution of the refund files, the direct incidence in the determination of the prices when the manager does not have the security in the quantity of the mount to return, the investment of the returned quantity for this concept dedicated ore to the acquisition of goods than in the amplification of the business, etc. The recommendation were carried out with the purpose of correcting the errors which were found when the investigation was concluded , proposing to the community alternatives of change in the normative environment, being this the only existent for the good use of the benefit.